Multi-market collusion with demand linkages and antitrust enforcement - Jay Pil Choi; Heiko A. Gerlach (Center for Economic Studies and ifo Institute (CESifo), 2009)
This paper analyzes dynamic cartel formation and antitrust enforcement when firms operate in demand-related markets. We show that cartel prosecution can have a knock-on effect: desisting a cartel in one market reduces profits and cartel stability and leads to the break-up of the cartel in the adjacent market. Cartel prosecution can also have a waterbed effect: desisting a cartel increases cartel stability in the adjacent market and induces cartel formation in previously competitive markets. We also consider policy implications of our analysis regarding an antitrust authority's investment decision in cartel enforcement.
Keywords: L13; L41; D43; 330; cartel formation; demand linkage; antitrust enforcement; Kartell; Wettbewerbsbeschränkung; Kartellverfahren; Nachfrage; Lieferanten-Kunden-Beziehung; Wirkungsanalyse; Theorie